EMT and tumor metastasis. Issue 1 (26th February 2015) - Heerboth, Sarah; Housman, Genevieve; Leary, Meghan; Longacre, Mckenna; Byler, Shannon; Lapinska, Karolina; Willbanks, Amber; Sarkar, Sibaji
Abstract: EMT and MET comprise the processes by which cells transit between epithelial and mesenchymal states, and they play integral roles in both normal development and cancer metastasis. This article reviews these processes and the molecular pathways that contribute to them. First, we compare embryogenesis and development with cancer metastasis. We then discuss the signaling pathways and the differential expression and down‐regulation of receptors in both tumor cells and stromal cells, which play a role in EMT and metastasis. We further delve into the clinical implications of EMT and MET in several types of tumors, and lastly, we discuss the role of epigenetic events that regulate EMT/MET processes. We hypothesize that reversible epigenetic events regulate both EMT and MET, and thus, also regulate the development of different types of metastatic cancers.